2012
DOI: 10.1111/j.1472-8206.2011.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of Croton zehntneri and its major constituent anethole display gastroprotective effect by increasing the surface mucous layer

Abstract: Croton zehntneri, a plant native to northeastern Brazil, is widely used in folk medicine to treat gastrointestinal problems and has rich essential oil content. The effects of the essential oil of Croton zehntneri (EOCZ) and its main constituent anethole on several models of gastric lesions were studied in mice and rats. Oral treatment with EOCZ and anethole, both at doses of 30-300 mg/kg, caused similar and dose-dependent gastroprotection against ethanol- and indomethacin-induced gastric damage, but did not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 51 publications
(77 reference statements)
0
34
0
Order By: Relevance
“…Preliminary findings have demonstrated that the Croton zehntneri leaves have a rich essential oil content that usually comprises 2-4% of the weight of dry leaves, varying with the hour of the day of the leaf collection, the season of the year and the region within northeast Brazil (Craveiro et al, 1994). Trans-anethole (AT) is the major constituent found in the essential oil of Croton zehntneri (EOCz) and is closely implicated with the pharmacologic activity attributed to EOCz (Albuquerque et al, 1995;Batatinha et al, 1995;Leal-Cardoso and Fonteles, 1999;Chainy et al, 2000;Oliveira et al, 2001;Carvalho et al, 2003;Rodrigues et al, 2009;Coelho-de-Souza et al, 2012). In indigenous medicine, teas and beverages made with the leaves of Croton zehntneri are used in the treatment of gastrointestinal disorders, as well as for anxiety and anorexia (Lazarini et al, 2000;Morais et al, 2006;Rodrigues et al, 2009;Coelho-de-Souza et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Preliminary findings have demonstrated that the Croton zehntneri leaves have a rich essential oil content that usually comprises 2-4% of the weight of dry leaves, varying with the hour of the day of the leaf collection, the season of the year and the region within northeast Brazil (Craveiro et al, 1994). Trans-anethole (AT) is the major constituent found in the essential oil of Croton zehntneri (EOCz) and is closely implicated with the pharmacologic activity attributed to EOCz (Albuquerque et al, 1995;Batatinha et al, 1995;Leal-Cardoso and Fonteles, 1999;Chainy et al, 2000;Oliveira et al, 2001;Carvalho et al, 2003;Rodrigues et al, 2009;Coelho-de-Souza et al, 2012). In indigenous medicine, teas and beverages made with the leaves of Croton zehntneri are used in the treatment of gastrointestinal disorders, as well as for anxiety and anorexia (Lazarini et al, 2000;Morais et al, 2006;Rodrigues et al, 2009;Coelho-de-Souza et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Trans-anethole (AT) is the major constituent found in the essential oil of Croton zehntneri (EOCz) and is closely implicated with the pharmacologic activity attributed to EOCz (Albuquerque et al, 1995;Batatinha et al, 1995;Leal-Cardoso and Fonteles, 1999;Chainy et al, 2000;Oliveira et al, 2001;Carvalho et al, 2003;Rodrigues et al, 2009;Coelho-de-Souza et al, 2012). In indigenous medicine, teas and beverages made with the leaves of Croton zehntneri are used in the treatment of gastrointestinal disorders, as well as for anxiety and anorexia (Lazarini et al, 2000;Morais et al, 2006;Rodrigues et al, 2009;Coelho-de-Souza et al, 2012). In addition, it has been claimed by local herbal dealers that the decoctions and cataplasms of the Croton zehntneri leaves are also used as local anti-inflammatory and healing agents (Matos et al, 1991;Leal-Cardoso and Fonteles, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, gastric wall mucus determination is useful for indicating gastric mucus secretion. 19,23 PPE significantly promoted gastric mucus content in the EtOH/HCl model, which suggests that the main gastroprotective activity of PPE is related to the protection of gastric mucus.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, they could prevent the disturbance in the gastric circulation generated by ethanol which caused a local vasocongestion with vascular stasis and mucosal damage associated to overproduction of oxygen-derived free radicals (16). Pretreatment with anethole (30 and 300 mg/kg) significantly increased mucus production by the gastric mucosa in the ethanol-induced ulcer model (17).…”
Section: Antinociceptive and Anti-inflammatory Activitymentioning
confidence: 91%